1998
DOI: 10.1096/fasebj.12.11.971
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects from exposure to dental amalgam Hg o : new distinctions between recent exposure and Hg body burden

Abstract: Potential toxicity from exposure to mercury vapor (Hg(o)) from dental amalgam fillings is the subject of current public health debate in many countries. We evaluated potential central nervous system (CNS) toxicity associated with handling Hg-containing amalgam materials among dental personnel with very low levels of Hg(o) exposure (i.e., urinary Hg <4 microg/l), applying a neurobehavioral test battery to evaluate CNS functions in relation to both recent exposure and Hg body burden. New distinctions between sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
1
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 29 publications
2
58
1
8
Order By: Relevance
“…There is some evidence for adverse behavioral effects associated with low mercury exposures ( Echeverria et al, 1998 ) and cognitive deficits in children due to methylmercury (Grandjean et al, 1997 ). On the other hand, there is no reasonable suspicion for health impairment caused by correctly posed amalgam fillings (Harhammer, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for adverse behavioral effects associated with low mercury exposures ( Echeverria et al, 1998 ) and cognitive deficits in children due to methylmercury (Grandjean et al, 1997 ). On the other hand, there is no reasonable suspicion for health impairment caused by correctly posed amalgam fillings (Harhammer, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported neurobehavioral effects related to motor and cognitive functions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in humans during ongoing exposure to mercury vapors. Contrary to the large number of studies on currently exposed workers, few epidemiologic studies have focused on the long-term effects on workers who are no longer exposed.…”
Section: Discussionmentioning
confidence: 99%
“…These tests mainly measure attention, motor speed, visual scanning and visuomotor tracking. They were not applied in the 2 neuropsychological studies of previously exposed workers (26,27), but poorer performance has been reported for currently exposed populations (16,18). It is an interesting observation that workers with high acute intensive exposure showed a substantial improvement in the test results of parts A and B after chelation with 2,3-dimercaptosuccinic acid (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Chronic exposure to lower concentrations of mercury can result in milder symptoms as well as detectable effects on motor function and behaviour, and previous studies have shown that relatively low levels of mercury exposure may be detrimental to health. 8,9 However, it is difficult to designate a threshold of exposure below which can be considered to be safe. For this reason and because local cases of symptomatic mercury poisoning of dentists had been detected, an occupational mercury monitoring programme was introduced in 1975 for dental practices in Scotland.…”
Section: Discussionmentioning
confidence: 99%